[OP.7C.02] BLOOD PRESSURE-ASSOCIATED POLYMORPHISMS IN SLC4A7 (SODIUM/BICARBONATE CO-TRANSPORTER NBCN1) ARE LINKED WITH GENE EXPRESSION AND INTRACELLULAR PH REGULATION. (September 2016) - Ng, F.; Bødtkjer, E.; Caulfield, M.J.; Ye, S.
Abstract : Objective: Genomewide-association studies have identified a number of loci influencing blood pressure, one of which is located near SLC4A7 (lead SNP rs13082711). SLC4A7 encodes an electroneutral Na+, HCO3− co-transporter, NBCn1, which contributes to intracellular pH (pHi) regulation in a range of tissues, including vascular smooth muscle and endothelium. Additionally, the NBCn1 knockout mouse demonstrates an altered blood pressure phenotype. We investigated the potential influence of SLC4A7 genotype on DNA-protein interaction, gene expression, and pHi regulation. Design and method: Primary cultures of human umbilical vein endothelial cells and artery smooth muscle cells of different SLC4A7 genotypes were used. DNA-protein interactions were identified by formaldehyde-associated isolation of regulatory elements (FAIRE), electrophoretic mobility shift assays (EMSA), and DNA-pulldown assays. Gene expression was quantified by allelic imbalance analyses and protein immunoblots. Intracellular acidification was induced by the ammonium-prepulse method. NBCn1 protein function was evaluated as Na+, HCO3− co-transport activity, based on the rate of dimethyl-amiloride-insensitive, Na+- and HCO3−-dependent pHi recovery. A10 rat aortic smooth muscle cells transfected with either 326E or 326K SLC4A7 variants were used to verify primary cultures results. Results: FAIRE studies showed that the chromatin of the risk allele was preferentially open, allowing increased transcription. EMSAs demonstrated allele-dependent interactions with nuclear proteins. Protein sequencing from DNA-pulldown assays failed to identify the nuclear proteins involved. Consistent with allele-dependent DNA-protein interactions, the risk allele was associated with increased NBCn1 mRNA and protein expression. Furthermore, increased NBCn1 expression in risk allele carriers was associated with increased in vitro protein function, as demonstrated by greater Na+, HCO3− co-transport activity during intracellular acidosis and higher baseline steady-state pHi compared to protective allele homozygotes. A10 cells overexpressing either 326E or 326K NBCn1 variants demonstrated equivalent increases in Na+, HCO3− co-transport activity, suggesting the amino acid change is less important than expression levels. Conclusions: We have outlined a potential mechanism for the SLC4A7 locus influencing blood pressure via NBCn1 gene transcription, protein expression, and pHi regulation of human vascular smooth muscle and endothelial cells. This effect appears independent of the associated E326K amino acid change.